ART REPORTING: CARTOONING IN THE PRINT MEDIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper examined cartooning in the print media as a form of reporting. Cartooning generally requires a measure of creativity and ability to depict issues and events in pictorial fashion. The use of cartoons has been a long standing feature of the print media, specifically newspapers and magazines. Caricature as a form of art had existed for a very long time in Nigeria before the belief that this form of satirisation in Nigeria is a colonial innovation. The Punch, The Guardian, This Day, The Sun, Vanguard, The Nation, Tell, Newswatch, etc., all publish cartoons and comic strips on social, political and economic affairs of the country or as illustrations of some editorial matter. Cartoons are funny drawings on newspapers and magazines making caricature of societal ills or maladministration. The primary function of the cartoon is communication. Cartoon was originally a sketch for a large canvas or fresco painting for architectural drawings, for tapestry design or for pictures in mosaic or glass. At present, cartoon has no doubt become an indispensable part of modern journalism. The article is however, anchored on two theories: social responsibility theory and agenda-setting theory. The researcher highlighted three major types of newspaper cartoons, which are: comic strips, political cartoons and gag cartoons. While considering the prominence and personality involved in drawing cartoon, the cartoonist also has to consider the timeliness of the issue being presented to the readers. The researcher identified some of the functions/roles of newspaper cartoons, among which is that cartoon provides readers with the platform of the formation of public opinion. The researcher concluded that cartoons published in newspapers are the critiques of the issues, personalities and institutions of the current situation as it can be said that cartoons are the chronicle of the current history. The researcher therefore, recommend that Art Reporting should be stand as a separate course in the field of mass communication just as Photography and Photojournalism, Investigative and Interpretative Reporting, Editorial Writing, Feature and Article Writing, and News Writing and Reporting.